PENATALAKSANAAN FISIOTERAPI ULTRA SOUND DAN TERAPI LATIHAN PADA KASUS CARPAL TUNNEL SYNDROME SINISTRA DI RSUD PROF. Dr. MARGONO SOEKARJO PURWOKERTO - Vega Indra Utama; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Abstract  Carpal  tunnel  syndrome  is  a  symptom  that  occurs  due  to  the  emphasis  on  N.  The  median  is  the cause of repetitive motion or trauma. The objectives to be achieved, namely, reduce pain, increase range of motion, increase muscle strength, and enhance the functional activity of the patient. The objectives are: increase muscle strength in the left wrist area, increase range of motion left wrist, and  restore  functional  activity  with  respect  to  the  functional  activity  of  the  left  hand. In  helping  to  overcome  these  problems  can  be  used  modalities  of  ultrasound  physiotherapy  and exercise therapy. And the results obtained at the end of therapy include: increased muscle strength, increase range of motion, and the enhancement of functional activity. Based therapy is carried out for 6 times to get the following results: (1) an increase in muscle strength of dorsal flexion of T1 to T6 = 4 = 5, Palmar flexion T1 to T6 = 3 = 4, (2) an increased range of motion Active dorso palmar flexion T1 = 50 º -0 º -55 º to T6 = 50 º -0 º -60 º. Keywords:  Carpal  Tunnel  Syndrome  Sinistra  with  U.S.  modalities  (ultra  sound)  and  exercise therapy.